Jack Fry's Interview - Anonymous (Online Ethics Center, 2006)
This case raises two primary issues: data sharing and recognition of the contributions of others, along with issues of collaboration, intellectual contribution and authorship.
Case Study / Scenario|Hypothetical / Fictional Case
Keywords: Authorship; Collaboration; Data Management; Interdisciplinary Research; Plagiarism; Publication Ethics; Research and Practice; Research Misconduct